2021
DOI: 10.1051/e3sconf/202128002003
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and economic aspects of sustainable development of Ukrainian regions

Abstract: The need for sustainable development of Ukrainian regions is due to the global threat of environmental degradation, the unstable situation in the world economy, low socio-economic indicators of the country and weak innovation activity. An important factor that has an influence on the economic development of regions is the ecological state of the environment. It plays one of the most important roles in the conducting of economic activities that require the use of natural resources. According to the results of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Our study found similar results, and that green and lowcarbon development is an inevitable requirement for sustainable development. Compared with the existing studies [39,40], this study has many advantages. First, emergy theory converts the energy that cannot be compared into the same unit, which directly reflects the relationship between the energy flow of each element in the system.…”
Section: Management Implicationsmentioning
confidence: 98%
“…Our study found similar results, and that green and lowcarbon development is an inevitable requirement for sustainable development. Compared with the existing studies [39,40], this study has many advantages. First, emergy theory converts the energy that cannot be compared into the same unit, which directly reflects the relationship between the energy flow of each element in the system.…”
Section: Management Implicationsmentioning
confidence: 98%
“…Therefore, based on China's basic national conditions and the objective needs of economic development [8], it is very important to study ULUE and analyze the relationship between ULUE and EDL for realizing the sustainable development of urban land and economy. For example, Babenko et al (2021) examined how the negative effects of land use and economic conditions affected the sustainable development of Ukraine [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the issue of climate change is crucial to agricultural development, which can lead to significant losses in agricultural production (Kadiyevskyy and Klymenko, 2014;Babenko et al, 2021). On the other hand, the yield indicator is related to the level of ploughed land, which exceeds all admissible values in Ukraine (Kaminskyi, 2018).…”
mentioning
confidence: 99%
“…However, while weather risks were able to induce food insecurity at the beginning of the research interval, such yield changes have almost no effect on food security, as the overall positive yield trend after 2003 has significantly improved the situation The model showed a significant positive contribution to grain yield (Table 3) of average precipitation in the March-May time interval, namely during the second growing season (х3). The null hypothesis (absence of this effect) is rejected at a significance level of 0.05 and a 1 per cent increase in precipitation leads to a yield increase of 0,06 hundreds kilograms per hectare: ̂= 11.99 + 0.05 1 + 0.06 3 (17) The practically oriented case of decreasing marginal utility of an agricultural input factors of production is considered (6,7). The econometric models are based on data on grain yields and the value of input factors of production (fertilizers, chemicals) for 1992-2017 (Table 4).…”
mentioning
confidence: 99%